MiR-126 affects the invasion and migration of glioma cells through GATA4. (18th August 2017) - Xu, Yifan; Xu, Wu; Lu, Tianyu; Dai, Yuxiang; Liang, Weibang
Abstract: We aimed to explore the relationship between miR-126 and glioma. miR-126 was highly expressed in low-grade clinical glioma tissue samples but lowly expressed in high-grade ones ( P  < .01). A human endogenous miR-126 expression vector was constructed. The migration capacity of cells transfected with the vector significantly decreased ( P  < .05). Up-regulation of miR-126 suppressed GATA4 protein expression. After transfection, they slightly contracted and became ovally or spherically shaped. F-actin significantly reduced, and microfilaments shortened or disappeared. The number of membrane-penetrating cells significantly decreased ( P  < .01). miR-126 inhibits the migration and invasion of glioma cells, which may be linked to GATA4 as a target gene.